2007
DOI: 10.1111/j.1537-2995.2007.01233.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mononuclear cells remaining in the leukoreduction system chambers of apheresis instruments after routine platelet collection: a new source of viable human blood cells

Abstract: The residual cell content of Trima Accel LRS chambers recovered after PLT collection is a good source of viable monocytes and lymphocytes. These PBMNCs, containing CD3+, CD14+, CD16+, CD19+, and CD34+ cells can be frozen to prepare cell banks, which opens new avenues for utilization in several physiologic studies or even in cellular therapy applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 29 publications
(50 reference statements)
7
52
1
1
Order By: Relevance
“…The obtained PBMC yield was in agreement with previous reports that used the Trima Accel device (Néron et al, 2007;Strasser et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The obtained PBMC yield was in agreement with previous reports that used the Trima Accel device (Néron et al, 2007;Strasser et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…Consequently, the availability of BC is increasingly scarce, and alternative sources to obtain cells for research purposes are needed. Néron et al (2007) have recently reported that the fraction of donor WBC retained in the leukoreduction chamber of the apheresis instrument represents a novel source of viable and functional populations of WBC, including monocytes. The functionality of cells recovered from PP was assessed in various experimental systems, and DC differentiation was achieved using a standard 7-day protocol (Dietz et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A maximum of 14 tubes from each patient were collected, pooled, and diluted in one volume of 10 mM phosphate-buffered saline, pH 7.4. Leukocytes from healthy individuals were recovered from leukoreduction systems, as described previously (Néron et al 2006;Néron et al 2007), after informed consent and following approval by the Research Ethics Committee of Héma-Québec. Peripheral blood mononuclear cells (PBMCs) were prepared from patients and controls by density centrifugation over Ficoll-Paque (GE Healthcare Bio--Sciences Inc., Baie d'Urfé, QC, Canada) (Fecteau and Néron 2003) and stored frozen until B-cell purification.…”
Section: Blood Sample Collection From Sle Patients and Healthy Indivimentioning
confidence: 99%
“…It is untenable to harvest onequarter or more of a donor's blood volume for obvious reasons. The adoption of apheresis systems by blood donation centers to collect plasma, platelets and other blood components provides a valuable source of viable primary human lymphocytes from peripheral blood through leukocyte reduction system (LRS) filters that are normally discarded following donation (26). In this manuscript we describe a method to purify CD16a from primary human NK cells from a single donor to analyze N-glycan composition.…”
Section: Introductionmentioning
confidence: 99%